Determinants of agricultural employment during the COVID-19 pandemic: A spatial analysis of Brazilian municipalities. - Patrícia Batistella; Luan Marca; Fernanda Castilhos França de Vasconcellos; Eduardo Rodrigues Sanguinet; Augusto Mussi Alvim; Adelar Fochezatto (PLoS ONE)
The impact of COVID-19 has extended beyond the health toll it has taken on populations. The global economy has experienced significant downturns, with unemployment rates reaching unprecedented highs for this century. Nonetheless, the agricultural sector has been uniquely affected by the pandemic, particularly given its crucial role in food supply. This study sought to examine the effects of the COVID-19 pandemic on agricultural employment in Brazilian municipalities. To achieve this, we employed a dataset spanning the period before and during the pandemic (2018-2021). Spatial econometrics was utilized to identify potential spatial factors linked to this occurrence. Notably, the findings reveal that the transfer policies implemented by the Brazilian Federal Government have had a positive impact on agricultural employment in Brazilian municipalities, challenging the common assumption that such measures might discourage job-seeking efforts. Moreover, the results suggest that the agricultural sector has managed to absorb individuals displaced from other sectors of the economy, demonstrating remarkable resilience in the face of economic challenges.